Synthesis and functional evaluation of chiral dendrimer-triamine-coordinated Gd complexes with polyaminoalcohol end groups as highly sensitive MRI contrast agents. Issue 26 (1st July 2015) - Miyake, Yuka; Kimura, Yu; Orito, Naomi; Imai, Hirohiko; Matsuda, Tetsuya; Toshimitsu, Akio; Kondo, Teruyuki
Abstract: Novel chiral dendrimer-triamine-coordinated Gd complexes with polyaminoalcohol end groups were synthesized and shown to have longitudinal relaxivity ( r 1 ) values 5 times higher than that of clinically used Gd-DTPA. The affinities of Gd-4a and Gd-4b for bovine serum albumin (BSA), respectively, were estimated by a quartz crystal microbalance (QCM) measurement. The amino groups of the dendrimer were then conjugated with PEG. This conjugation with PEG strongly affected its ability to attenuate signals in T 1 -weighted MRI. Graphical abstract: